Macromedia Flash Professional 8 game graphics - Firebaugh, Robert (Charles River Media, 2007)
Creating graphics for Flash games can be fun and rewarding, especially when you can channel your imagination into your art and provide potential players with a fun entertainment experience. Written for anyone creating games with Flash, Macromedia Flash(TM) Professional 8 Game Graphics teaches the essentials of Flash game art. You'll learn all about what Flash graphics are, how to create your own, and how to import them into working game source files. The book covers vector and raster graphics and explains how both can be used to improve the performance of your game. Helpful tips and techniques are included throughout to help you become more efficient at creating user interfaces, game character sprites, and special effects. And several real-world game examples are used to teach about the development process for creating game graphics and preparing them correctly for a smooth transition to programming. You don't have to be an artist to use this book, because the graphic techniques taught don't require a painter's hand. So if you want to create awesome graphics for your Flash games, this is the place to get started